asadrazanayani

asadrazanayani

Forum Replies Created

Viewing 1 post (of 1 total)
  • Author
    Posts
  • asadrazanayani 1asadrazanayani
    Participant
    Up
    5
    Down

    I personally like to draw out a diagram, so

    Ber..jpg

    We have been asked to calculate the P(decline assuming -ve ratio).

    The key realization is: P(-ve ratio and decline) = P(decline and -ve ratio)

    Now: P(-ve ratio and decline) = P(-ve ratio assuming decline) x P(decline) = P(decline and -ve ratio) = P(decline assuming -ve ratio) x P(-ve ratio)

    Therefore: P(-ve ratio assuming decline) x P(decline) = P(decline assuming -ve ratio) x P(-ve ratio)

    We can calculate P(-ve ratio) as

    P(-ve ratio) = (P(-ve ratio assuming decline) x P(decline)) + (P(-ve ratio assuming not decline) x P(not decline))

    We can now replace

    P(decline assuming -ve ratio) = (P(-ve ratio assuming decline) x P(decline)) / (P(-ve ratio assuming decline) x P(decline)) + (P(-ve ratio assuming not decline) x P(not decline))

    P(decline assuming -ve ratio) = 0.9 x 0.2 / ((0.9 x 0.2) + (0.8 x 0.1))

    P(decline assuming -ve ratio) = 0.6923076923

Viewing 1 post (of 1 total)